2013
DOI: 10.1002/jnr.23202
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MCP‐1 and fractalkine on endothelial cells and astrocytes may contribute to the invasion and migration of brain macrophages in ischemic rat brain lesions

Abstract: Some macrophages expressing NG2 chondroitin sulfate proteoglycan (NG2) and the macrophage marker Iba1 accumulate in the ischemic core of a rat brain subjected to transient middle cerebral artery occlusion (MCAO) for 90 min. These cells are termed BINCs (for brain Iba1(+) /NG2(+) cells) and may play a neuroprotective role. Because BINCs are bone marrow-derived cells, they are able to invade ischemic tissue after the onset of an ischemic insult. In this study, chemokine-based mechanisms underlying the invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
2
33
1
Order By: Relevance
“…While CCL2 concentrations were significantly similarly augmented in the acute ischemic brain, the cellular source of this chemokine was not assessed. Previous studies support a strong role for endothelial cells and astrocytes as important mediators of monocyte recruitment [37, 84]. Our findings also highlight the importance of modeling stroke injury in aged mice as the finding of this biased recruitment of neutrophils in older mice represents an important translational advance for therapeutic discovery that would not have been seen if only young mice were evaluated.…”
Section: Discussionsupporting
confidence: 83%
“…While CCL2 concentrations were significantly similarly augmented in the acute ischemic brain, the cellular source of this chemokine was not assessed. Previous studies support a strong role for endothelial cells and astrocytes as important mediators of monocyte recruitment [37, 84]. Our findings also highlight the importance of modeling stroke injury in aged mice as the finding of this biased recruitment of neutrophils in older mice represents an important translational advance for therapeutic discovery that would not have been seen if only young mice were evaluated.…”
Section: Discussionsupporting
confidence: 83%
“…Having demonstrated that A20 KO mice suffer important gliosis, we checked the status of brain EC in these mice. As anticipated, astrogliosis and microglial activation corresponded with overt EC activation in A20 KO brain vasculature, as demonstrated by increased expression of the adhesion molecules VCAM-1, ICAM-1 and endothelial specific E-selectin, as well as the chemokine MCP-1, although the latter may be a product of glial cells, in addition to EC [75]. Increased endothelial activation in brains of A20 KO mice is in keeping with the well-documented anti-inflammatory and homeostatic function of A20 in EC [15,76], and agrees with our recent data demonstrating that mere partial loss of A20 aggravates the inflammatory phenotype of the endothelium in a vascular allograft model of transplant arteriosclerosis (Lee et al ., manuscript in preparation).…”
Section: Discussionmentioning
confidence: 64%
“…For instance, CXCL1 stimulates chemoattraction of neutrophils into the damaged areas [7]. CCL2 and CX3CL (fractalkine) alter the permeability of the blood brain barrier (BBB), promote migration of both macrophages [8] and bone marrow-derived stem cells into ischemic cerebral areas, and contribute to the regeneration of the injured area [9]. CCL3 and CCL4, which are increased 6 hours after ischemia, recruit lymphocytes, macrophages, and microglia [10, 11].…”
Section: Introductionmentioning
confidence: 99%